STUDENTS’ PERCEPTION OF THE ROLE OF TEACHING STRATEGIES ON STUDENTS’ ENGLISH LEARNING MOTIVATION - Nur, A. Dwi Anugrah; Muliati, A.; Muhalim, Muhalim (Universitas Negeri Makassar, 2024)
There are two objectives in this study, namely: 1) to find out how teaching strategies motivate students in English classes. 2) students' perceptions regarding the role of teaching strategies on their English learning motivation. This research is a type of mixed qualitative and quantitative research (mixed method) that employs a standard survey method for quantitative data collection and a descriptive method for qualitative data collection in order to determine how and what students think about the role of teachers' teaching strategies on students' motivation to learn English. The study's participants were students in grades 10 A and 10 B at SMK Negeri 2 Soppeng, and it used two types of instruments: Google Forms and interviews. The snowball technique was employed for interview sampling, with the first student chosen by the English teacher who taught in both classes, followed by the first interviewee, and so on. 1) The study's findings demonstrated that teaching strategy is one of the primary elements influencing students' learning motivation. Teachers must be highly skilled and creative in order to motivate pupils to be more active and involved in their education. This study reveals that the majority of positive facts from students indicate that English teachers who teach in the two classes have been able to motivate students to interact and build a sense of passion. 2) As a result of detailing the three types of teaching tactics used by the teacher, the students experienced a variety of benefits that improved the efficacy of their learning. Furthermore, it can boost students' passion for studying and give them the impression that learning English will have a significant impact on their lives in the long run.